Ruthenium-doped nanoneedle sheet carbon-loaded cobaltosic oxide self-supporting electrode and preparation method and application thereof
By performing trace ruthenium doping and hydrothermal preparation in Co-based catalysts, a ruthenium doped nanoneedle sheet carbon-supported cobalt tetroxide self-supported electrode was formed, which solved the problem of insufficient catalyst conductivity and active site exposure, and achieved excellent oxygen evolution catalytic reaction activity and stability, which was suitable for OER catalysis.
Patent Information
- Application Number
- CN202411527244.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The existing Co-based OER catalysts have insufficient conductivity and insufficient exposure of active sites, which limits the further improvement of catalyst performance and commercialization process.
The ruthenium doping is performed by a one-pot hydrothermal method to form a ruthenium cobalt precursor, and then dried and calcined and oxidized in air to prepare a ruthenium-doped nanoneedle sheet carbon-carrying cobalt tetraoxide (RCO) self-supporting electrode. The catalyst has a continuous open interface, element doping and carbon cloth support.
It significantly improves the activity and stability of the oxygen evolution catalytic reaction of the catalyst, and has better performance than commercial RuO2 catalysts, and is suitable for OER catalysis under alkaline and acidic conditions.
Smart Images

Figure CN119615244A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of electrocatalysts, and in particular to a ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide (RCO) self-supporting electrode and a preparation method and application thereof. Background Art
[0002] Climate warming has been spreading around the world for a long time and has become a major crisis that cannot be ignored in the new era. The development of green and long-lasting energy to replace traditional fossil energy has become the focus of attention. One of the most promising alternatives to alleviate the problems associated with fossil fuels is electrochemical storage devices and energy conversion devices. Clean energy such as wind energy, solar energy, and tidal energy have problems such as intermittency in the power generation process, which has become a major technical problem hindering their further development. The generated electricity is directly stored through metal-air batteries, or used for water electrolysis to produce hydrogen, and converted into chemical energy storage of hydrogen. Hydrogen is considered to be a renewable secondary energy source to replace fossil fuels because of its zero carbon dioxide emissions and high energy density during production and application. The oxygen evolution reaction at the anode of water electrolysis to produce hydrogen is a four-point process with a slow kinetic rate. Ru / Ir-based catalysts are often used to improve the reaction efficiency, but the reserves of precious metals are scarce and expensive. There is an urgent need to develop low-cost, highly active and stable oxygen evolution reaction (OER) catalysts.
[0003] In recent years, Co-based OER catalysts have become a hot topic in the research of OER electrocatalysts due to their unique morphology, porous structure, and excellent chemical and mechanical stability. However, problems such as insufficient conductivity of the catalyst and insufficient exposure of active sites have limited the further improvement of the catalyst performance and hindered the commercialization of the catalyst. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide (RCO) self-supporting electrode and its preparation method and application. A trace amount of ruthenium is doped by a one-pot hydrothermal method to form a ruthenium cobalt precursor, which is then dried and calcined and oxidized in air to prepare a trace amount of ruthenium-doped cobalt tetroxide nanoneedle sheet self-supporting electrode. The continuous open interface, element doping and carbon cloth support of the catalyst enable the catalyst to exhibit excellent oxygen evolution catalytic reaction activity and stability.
[0005] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:
[0006] A method for preparing a ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide (RCO) self-supporting electrode comprises the following steps:
[0007] Step 1, weighing ammonium fluoride, cobalt nitrate hexahydrate, ruthenium trichloride and urea, dissolving them in deionized water, and continuously stirring to obtain a uniform mixed solution;
[0008] Step 2, cutting the carbon cloth and pre-treating it;
[0009] Step 3, placing the treated carbon cloth and the mixed solution of step 1 in a hydrothermal reactor, performing a hydrothermal reaction at 120-160° C. for 3-5 hours, and then naturally cooling the carbon cloth grown with the ruthenium cobalt precursor, taking it out and washing it with deionized water and ethanol, and then drying it to obtain a semi-finished product for standby use;
[0010] Step 4, placing the semi-finished product in a tube furnace, and heating it in air for low-temperature oxidation, and naturally cooling it to obtain a ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide (RCO) self-supporting electrode.
[0011] As an improvement, in step 1, the molar ratio of ruthenium trichloride, urea, cobalt nitrate hexahydrate and ammonium fluoride is 0.0012:5:1:2.
[0012] As an improvement, the pretreatment steps in step 2 are: ultrasonically clean the cut carbon cloth with acetone, ethanol, and deionized water in turn to remove impurities on the surface of the carbon cloth and complete the pre-activation of the carbon cloth; in order to further activate and enhance the hydrophilicity of the carbon cloth, the cleaned carbon cloth needs to be ultrasonically oxidized again in nitric acid; after the activation of the carbon cloth, it needs to be ultrasonically cleaned in distilled water; finally, the pretreated carbon cloth is placed in distilled water for standby use.
[0013] A further improvement is that the size of the carbon cloth is 2cm×4cm; the specific operations for cleaning and activating the surface of the carbon cloth are: ultrasonically cleaning the carbon cloth with acetone, ethanol, and deionized water for 30 minutes respectively, and then rinsing it repeatedly with deionized water for 3 times after ultrasonication, each time for 5 minutes; the concentration of concentrated nitric acid used for immersion is 14M, and ultrasonic oxidation is performed for 30 minutes.
[0014] As an improvement, the heating rate of the tubular furnace in step 4 is 2°C min -1 , rise to 200℃-300℃ for low temperature oxidation for 4h.
[0015] The ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide (RCO) self-supporting electrode prepared by the preparation method has a continuous nanoneedle sheet structure, and the nanosheets composed of cobalt tetroxide on the carbon carrier are evenly distributed.
[0016] The ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide (RCO) self-supporting electrode prepared by the above preparation method is used in electrocatalysis of water.
[0017] Beneficial effects:
[0018] Compared with the prior art, the ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide (RCO) self-supporting electrode and its preparation method and application in the present invention have the following advantages:
[0019] 1. The present invention adopts a hydrothermal method combined with low-temperature calcination to prepare a RCO self-supporting electrode catalyst. The preparation method is mature and can be mass-produced. Trace amounts of ruthenium doping further reduce the use of precious metals and reduce production costs. The prepared RCO catalyst grows on carbon cloth to form a self-supporting electrode, which has a nano-needle thin-sheet open interface and provides a large number of active sites. Trace amounts of ruthenium doping effectively optimize the electron transport of the catalyst and further enhance the activity of the catalyst. After air calcination and oxidation, the stability of the self-supporting electrode is also greatly improved.
[0020] 2. The present invention prepares a trace amount of ruthenium-doped nanoneedle thin sheet cobalt tetroxide self-supporting electrode material, and its OER catalytic performance under alkaline and acidic conditions far exceeds that of commercial RuO 2 , can be widely used in the field of electrocatalytic water decomposition. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 X-ray diffraction (XRD) patterns of the catalysts prepared in Example 1 and Comparative Example 1;
[0022] Figure 2 The scanning electron microscope (SEM) and high-resolution transmission electron microscope (HRTEM) images of the catalyst prepared in Example 1;
[0023] Figure 3 XPS graph of the ruthenium-doped nanoneedle sheet carbon-supported cobalt tetraoxide (RCO) self-supporting electrode prepared in Example 1, wherein (a) is the overall spectrum of RCO 140-5250-4, (b) is the oxygen element spectrum of RCO 140-5250-4, (c) is the cobalt element spectrum of RCO 140-5250-4, and (d) is the ruthenium element spectrum of RCO 140-5250-4;
[0024] Figure 4 For Examples 1-7, Comparative Example 1 and RuO 2 OER performance diagram of the prepared catalyst under alkaline conditions;
[0025] Figure 5 For Examples 1-7, Comparative Example 1 and RuO 2 Performance of the prepared catalyst under alkaline conditions, where (a) is the Tafel curve and (b) is the ECSA curve;
[0026] Figure 6 For Example 1 and RuO 2 The stability characterization results of the prepared catalyst under alkaline conditions;
[0027] Figure 7 For Examples 1-7, Comparative Example 1 and RuO 2OER performance diagram of the catalyst under acidic conditions, where (a) is the LSV curve and (b) is 10 mA cm -2 Lower overpotential;
[0028] Figure 8 For Examples 1-7, Comparative Example 1 and RuO 2 Performance of the prepared catalyst under acidic conditions, where (a) is the Tafel curve and (b) is the ECSA curve;
[0029] Fig. 9 For Example 1 and RuO 2 The stability characterization results of the prepared catalyst under acidic conditions. DETAILED DESCRIPTION
[0030] The following examples will enable those skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0031] The OER test method in the embodiment of the present invention is: the ruthenium-doped nanoneedle sheet carbon-supported cobalt oxide (RCO) self-supporting electrode is used as the working electrode, and the Ag / AgCl electrode and the carbon rod are used as the reference electrode and the counter electrode, respectively, to characterize the electrochemical activity and stability in 1M KOH solution and 0.1M sulfuric acid solution. 2 The source was purchased from Shanghai Alpha Biotechnology Co., Ltd.
[0032] Example 1
[0033] (1) Weigh 1.2 g (4 mmol) of Co(NO 3 ) 2 6H 2 O, 0.3 g (8 mmol) NH 4 F. 1.2 g (20 mmol) of urea and 1 mg (0.0048 mmol) of ruthenium trichloride were dissolved in 35 mL of deionized water, and stirred continuously to obtain a uniformly dispersed mixed solution;
[0034] (2) The carbon cloth is cut into a length and width size of 2cm×4cm. The carbon cloth is ultrasonically cleaned with acetone, ethanol, and deionized water for 30 minutes respectively to remove impurities on the surface of the carbon cloth and complete the pre-activation of the carbon cloth. In order to further activate and enhance the hydrophilicity of the carbon cloth, the cleaned carbon cloth needs to be ultrasonically oxidized again in 14M nitric acid for 30 minutes. After the activation of the carbon cloth, it needs to be ultrasonically cleaned in distilled water for 3 times, each time for 5 minutes. Finally, the pretreated carbon cloth is placed in distilled water for use;
[0035] (3) The treated carbon cloth and the mixed solution of step 1 are placed in a hydrothermal reactor, and the hydrothermal reaction is carried out at 140° C. for 5 h. After natural cooling, the carbon cloth grown with the ruthenium cobalt precursor is taken out and washed with deionized water and ethanol until neutral, and then placed in an oven at 60° C. for 4 h to obtain a semi-finished product for standby use.
[0036] (4) Place the semi-finished product in a tube furnace at 2°C min -1 The temperature was raised to 250°C at a rate of 100 °C and then oxidized in air for 4 h. After cooling, a ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide (RCO) self-supporting electrode was obtained, which was recorded as RCO 140-5250-4.
[0037] The ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide (RCO) self-supporting electrode prepared in Example 1 was characterized, and the XRD spectrum was as follows: Figure 1 As shown, the Co obtained during the preparation process 3 O 4 The precursor corresponds to the standard card PDF#43-1003; the microstructure of the catalyst was characterized by SEM and TEM, such as Figure 2 As shown, the obtained catalyst has a continuous nanoneedle thin sheet structure, and the nanosheets composed of cobalt tetroxide on the carbon carrier are evenly distributed, which is conducive to exposing more active sites and enhancing the material transport in the catalytic reaction and the conductivity of the catalyst.
[0038] Figure 3 This is the high-resolution XPS spectrum of the ruthenium-doped nanoneedle thin sheet carbon-supported cobalt oxide (RCO) self-supporting electrode. The overall spectrum in (a) shows that the catalyst mainly contains elements such as O, Co, and Ru.
[0039] Comparative Example 1
[0040] Except that step (1) does not contain ruthenium trichloride, the rest is the same as Example 1 to obtain CO black carbon cloth, which is recorded as CO 140-5250-4.
[0041] Example 2
[0042] Except that the temperature of the hydrothermal reaction in step (3) was changed to 120° C., the rest was the same as in Example 1 to obtain RCO black carbon cloth, which was recorded as RCO 120-5250-4.
[0043] Example 3
[0044] Except that the temperature of the hydrothermal reaction in step (3) was changed to 160° C., the rest was the same as in Example 1 to obtain RCO black carbon cloth, which was recorded as RCO 160-5250-4.
[0045] Example 4
[0046] Except that the hydrothermal reaction time was changed to 3 h, the rest was the same as in Example 1 to obtain RCO black carbon cloth, which was recorded as RCO 140-3250-4.
[0047] Example 5
[0048] Except that the hydrothermal reaction time was changed to 7 h, the rest was the same as in Example 1 to obtain RCO black carbon cloth, which was recorded as RCO 140-7250-4.
[0049] Example 6
[0050] Except that the temperature of low-temperature oxidation in step (4) is 200° C., the rest is the same as in Example 1, to obtain RCO black carbon cloth, denoted as RCO 140-5200-4.
[0051] Example 7
[0052] Except that the temperature of low-temperature oxidation in step (4) is 300° C., the rest is the same as in Example 1 to obtain RCO black carbon cloth, which is recorded as RCO 140-5300-4.
[0053] The OER polarization curves of the catalysts prepared in Examples 1-7 and Comparative Example 1 were tested. The results are as follows: In 1M KOH solution, RCO 140-5250-4 prepared in Example 1 has an OER polarization curve of 10 mA cm -2 The overpotential at the current density is 186 mV, which is significantly lower than that of RuO 2 The overpotential value of the catalyst (538mV) Figure 4 ), the Tafel slope value is 184mV dec -1 , smaller than RuO 2 (300mVdec -1 )( Figure 5 ), indicating that RCO 140-5250-4 has a faster electrochemical reaction rate. After 26h of stability test under constant voltage, RCO 140-5250-4 still retained 72.5% of the initial current, which is much stronger than commercial RuO 2 45.3% ( Figure 6 ). In 0.1 M sulfuric acid solution, RCO 140-5250-4 has a conductivity of 10 mA cm -2 The overpotential at the current density is 127 mV, which is significantly lower than that of RuO 2 The overpotential value of the catalyst (397mV) Figure 7 After 48 hours of stability test under constant voltage, the catalyst RCO 140-5250-4 still retained 70% of the initial current, which is much stronger than commercial RuO 2 37% ( Fig. 9 ).
[0054] In alkaline electrolyte, CO 140-5250-4 prepared in Comparative Example 1 was -2 The overpotential at the current density is 225 mV, which is significantly lower than that of RuO 2 The overpotential value of the catalyst (538mV) Figure 4 ), in acid electrolyte, CO 140-5250-4 at 10mAcm -2 The overpotential at the current density is 407 mV, slightly higher than that of RuO 2 The overpotential value of the catalyst (397mV) Figure 7 ).
[0055] In alkaline electrolyte, RCO 120-5250-4 prepared in Example 2 was -2 The overpotential at the current density is 354 mV, which is significantly lower than that of RuO 2 The overpotential value of the catalyst (538mV) Figure 4 ); In acidic electrolyte, RCO 120-5250-4 at 10 mA cm -2 The overpotential at the current density is 410 mV, slightly higher than that of RuO 2 The overpotential value of the catalyst (397mV) Figure 7 ).
[0056] In alkaline electrolyte, RCO 160-5250-4 prepared in Example 3 was -2 The overpotential at the current density is 377 mV, which is significantly lower than that of RuO 2 The overpotential value of the catalyst (538mV) Figure 4 ), in acid electrolyte, RCO 160-5250-4 at 10 mA cm -2 The overpotential at the current density is 398mV, which is close to RuO 2 The overpotential value of the catalyst (397mV) Figure 7 ).
[0057] In alkaline electrolyte, RCO 140-3250-4 prepared in Example 4 was -2 The overpotential at the current density is 304 mV, which is significantly lower than that of RuO 2 The overpotential value of the catalyst (538mV) Figure 4 ), in acid electrolyte, RCO 140-3250-4 at 10 mA cm -2 The overpotential at the current density is 264 mV, which is significantly lower than that of RuO 2 The overpotential value of the catalyst (397mV) Figure 7 ).
[0058] In alkaline electrolyte, RCO 140-7250-4 prepared in Example 5 has a -2 The overpotential at the current density is 367 mV, which is significantly lower than that of RuO 2 The overpotential value of the catalyst (538mV) Figure 4 ), in acid electrolyte, RCO 140-7250-4 at 10 mA cm -2 The overpotential at the current density is 299 mV, which is significantly lower than that of RuO 2 The overpotential value of the catalyst (397mV) Figure 7 ).
[0059] In alkaline electrolyte, RCO 140-5200-4 prepared in Example 6 has a -2 The overpotential at the current density is 336 mV, which is significantly lower than that of RuO 2 The overpotential value of the catalyst (538mV) Figure 4 ), in acidic electrolyte, RCO 140-5200-4 at 10 mA cm -2 The overpotential at the current density is 436 mV, which is significantly higher than that of RuO 2 The overpotential value of the catalyst (397mV) Figure 7 ).
[0060] In alkaline electrolyte, RCO 140-5300-4 prepared in Example 7 was -2 The overpotential at the current density is 228 mV, which is significantly lower than that of RuO 2 The overpotential value of the catalyst (538mV) Figure 4 ), in acidic electrolyte, RCO 140-5300-4 at 10 mA cm -2 The overpotential at the current density is 326 mV, which is significantly lower than that of RuO 2 The overpotential value of the catalyst (397mV) Figure 7 ).
[0061] In summary, the present invention uses a one-pot hydrothermal method to form a ruthenium-cobalt precursor by trace ruthenium doping, and then calcining and oxidizing in air after drying to prepare a trace ruthenium-doped cobalt tetroxide nanoneedle thin sheet self-supporting electrode. The continuous open interface, element doping and carbon cloth support of the catalyst make the catalyst exhibit excellent oxygen evolution catalytic reaction activity and stability, and has good application prospects.
Claims
1. A method for preparing a ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide self-supporting electrode, characterized in that: The following steps are involved: Step 1, weighing ammonium fluoride, cobalt nitrate hexahydrate, ruthenium trichloride and urea, dissolving them in deionized water, and continuously stirring to obtain a uniform mixed solution; Step 2, cutting the carbon cloth and pre-treating it; Step 3, placing the treated carbon cloth and the mixed solution of step 1 in a hydrothermal reactor, performing a hydrothermal reaction at 120-160° C. for 3-5 hours, and then naturally cooling the carbon cloth grown with the ruthenium cobalt precursor, taking it out and washing it with deionized water and ethanol, and then drying it to obtain a semi-finished product for standby use; Step 4, placing the semi-finished product in a tubular furnace, and heating it in air for low-temperature oxidation, and obtaining a ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide self-supporting electrode after natural cooling.
2. The method for preparing a ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide self-supporting electrode according to claim 1, characterized in that: In step 1, the molar ratio of ruthenium trichloride, urea, cobalt nitrate hexahydrate and ammonium fluoride is 0.0012:5:1:
2.
3. The method for preparing a ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide self-supporting electrode according to claim 1, characterized in that: The pretreatment steps described in step 2 are: ultrasonically clean the cut carbon cloth with acetone, ethanol, and deionized water in turn to remove impurities on the surface of the carbon cloth and complete the pre-activation of the carbon cloth; in order to further activate and enhance the hydrophilicity of the carbon cloth, the cleaned carbon cloth needs to be ultrasonically oxidized again in nitric acid; after the activation of the carbon cloth, it needs to be ultrasonically cleaned in distilled water; finally, the pretreated carbon cloth is placed in distilled water for use.
4. The method for preparing a ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide self-supporting electrode according to claim 3, characterized in that: The size of the carbon cloth is 2cm×4cm; the specific operations of cleaning and activating the surface of the carbon cloth are: using acetone, ethanol, and deionized water to ultrasonically clean the carbon cloth for 30 minutes respectively, and then rinsing it repeatedly with deionized water for 3 times after ultrasonication, each time for 5 minutes; the concentration of concentrated nitric acid used for immersion is 14M, and ultrasonic oxidation is performed for 30 minutes.
5. The method for preparing a ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide self-supporting electrode according to claim 1, characterized in that: The heating rate of the tubular furnace in step 4 is 2°C min -1 , rise to 200℃-300℃ for low temperature oxidation for 4h.
6. A ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide self-supporting electrode prepared by any one of the preparation methods described in claims 1-5, characterized in that: The ruthenium-doped nano-needle sheet carbon-supported cobalt tetroxide self-supporting electrode has a continuous nano-needle sheet structure, and the nano-sheets composed of cobalt tetroxide on the carbon carrier are evenly distributed.
7. Application of a ruthenium-doped nanoneedle sheet carbon-supported cobalt tetroxide self-supporting electrode prepared by any one of the preparation methods described in claims 1-5 in electrocatalysis of water.
Citation Information
Patent Citations
Metal-doped self-supporting cobalt tetroxide nano array catalyst as well as preparation method and application thereof
CN118028890A
Ruthenium-doped cobaltosic oxide catalyst for hydrogen production through electro-catalysis water splitting, preparation method and application
CN118272849A
Preparation method of nitrogen-doped carbon modified self-supporting La-doped Co3O4 oxygen evolution catalyst
CN118345429A
Cited By
Cobaltosic oxide loaded ruthenium dioxide fiber as well as preparation method and application thereof
CN120119281A
Preparation method of RuSe2 / RuO2-coated CC heterojunction full-hydrolysis self-supporting electrode
CN122039135A